Mortality During Total Hip Periprosthetic Joint Infection - Natsuhara, Kyle M.; Shelton, Trevor J.; Meehan, John P.; Lum, Zachary C. (The Journal of arthroplasty, 2019)
We sought to understand the mortality rate of periprosthetic joint infection (PJI) of the hip undergoing 2-stage revision for infection. Database search, yielding 23 relevant studies, totaled 19,169 patients who underwent revision for total hip PJI. One-year weighted mortality rate was 4.22% after total hip PJI. Five-year mortality was 21.12%. Average age was 65 years. When comparing the national age-adjusted risk of mortality and the reported 1-year mortality risk in this systematic review, the risk of death after total hip PJI is significantly increased (odds ratio 3.58, P < .001). The mortality rate during total hip revision for infection is high. When counseling a patient regarding complications of this disease, death should be discussed.